Management Audit of Inventory Function (Case Study at Bigland Hotel Bogor) - Iqbal Assidiq, Muhammad; Indupurnahayu, Indupurnahayu; Hurriyaturrohman, Hurriyaturrohman (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2022)
The purpose of this study is: 1) To identify whether the company has a policy procedure related to its inventory function. 2) To assess whether the activities of the inventory function are already running in accordance with the policy procedures established. The approach in this study is qualitative approach, the research technique used is descriptive qualitative with the type of case study research. The data sources of this study are primary and secondary data. Data collection techniques in obtaining the data needed by researchers are interviews, observations, and documentation. The results of the study found that there are weaknesses including: 1) Inadequate storage of goods, 2) Recording on bin cards need to be re-recorded, 3) Errors up to negligence made by the User Department when making requests for goods in the Warehouse. The author can conclude that the inventory function at Bigland Hotel Bogor is already running well. This is evidenced by the policy of Standard Operational Procedure (SOP) which is clearly documented, as evidenced by the existence of internal control systems in the company. The policy has been almost adhered to by every staff. However, there are still weaknesses that may result in losses for the company. In order for the company to run better, the author provides recommendations such as following up on the expansion of the Warehouse area to minimize the loss of goods in the Warehouse, conduct training related to Store Requisition (SR) procedures, and follow up on the re-entry plan on the inventory card (bin card).